Hypotensive and sedative effects of insulin in autonomic failure. Issue 6591 (18th July 1987) - Mathias, C J; da Costa, D F; Fosbraey, P; Christensen, N J; Bannister, R
Abstract : The haemodynamic responses to intravenous insulin (0.15 units/kg) were measured in five patients with chronic autonomic failure who were not receiving drug treatment. After the administration of insulin supine blood pressure fell steadily, with a substantial reduction even before the onset of hypoglycaemia. None of the patients showed the usual range of neuroglycopenic symptoms, but they all became drowsy, with increasing sedation as the blood glucose concentration fell. In four other patients with autonomic dysfunction intravenous injection of 25-50 ml of 50% glucose alone caused a striking, although transient, fall in blood pressure. Hypoglycaemia was reversed by a 10 minute intravenous infusion of 100 ml of 25% glucose; this did not lower blood pressure further and rapidly restored previous levels of alertness. Consideration must be given to the hypotensive potential of insulin in patients with autonomic failure during an insulin stress test. The inability of these patients to show the usual manifestations of hypoglycaemia, plus the short lived, though pronounced, reduction in blood pressure after intravenous administration of 50% glucose, may further increase the risks of this procedure.